RESEARCH OF DIFFUSIVE ALLOYED SELFFLUXING POWDERS ON THE BASIS OF STEELS OF AN AUSTENITIC CLASS - A. F. Panteleenko; O. G. Devoyno (Литьë и металлургия)
Researches of diffuse-alloyed self-fluxing powders, based on austenitic steels, suggest that the resulting material will have high dyuromatricheskimi characteristics that allow its use for wear-resistant coatings.